Pengaruh Struktur Modal dan Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2021 - 2023 - Nurul Hidayah; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to determine the effect of capital structure and company size on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) in 202 1-2023. This type of research is quantitative. The population of this study was all companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sampling technique used was purposive sampling, resulting in 75 companies as research samples. The data analysis technique used was multiple linear regression analysis using SPSS 20. The results of the partial effect hypothesis test (t-test) showed that capital structure had a negative and significant effect on company financial performance, while company size had a positive and significant effect on company financial performance.